2019
DOI: 10.1186/s41983-019-0127-2
|View full text |Cite
|
Sign up to set email alerts
|

Serum and urine ghrelin in adult epileptic patients

Abstract: Background: Several neuropeptides have concerned with epilepsy pathogenesis; ghrelin showed an anticonvulsant effect. There is a potential relation between its level and antiepileptic drug (AEDs) response.Objective: To evaluate ghrelin effect in adult epileptic patients and in response to AEDs. Materials and methods: This case control study included 40 adult epileptic patients and 40 healthy controls. Participants were subjected to history taking of seizure semiology, full general and neurological examination,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…To our knowledge, this is the first time that the ghrelin-to-DAG ratio has been found to be specifically affected in children with generalized epilepsy. Indeed, similar results were reported only in adult patients with a history of generalized seizures [28][29][30] by some, but not all, investigators [31,32] and, especially, no data were available before the drug treatment [5].…”
Section: Discussionsupporting
confidence: 65%
“…To our knowledge, this is the first time that the ghrelin-to-DAG ratio has been found to be specifically affected in children with generalized epilepsy. Indeed, similar results were reported only in adult patients with a history of generalized seizures [28][29][30] by some, but not all, investigators [31,32] and, especially, no data were available before the drug treatment [5].…”
Section: Discussionsupporting
confidence: 65%
“…The serum DAG levels did not differ after three months of ASD treatment, while the AG levels were decreased after three months [ 80 ]. Finally, ASD-responsive patients had increased ghrelin levels compared to nonresponders in two studies, but not in another study [ 82 , 86 , 89 ]. A significant positive correlation has been shown between both the AG and DAG levels and disease duration, which could be indicative of ghrelin resistance, but could also be related to ASD use [ 84 ].…”
Section: Studies In Humansmentioning
confidence: 95%
“…Three studies demonstrated that patients suffering from focal epilepsy had higher ghrelin plasma levels compared to patients suffering from generalized seizures [ 80 , 81 , 85 ]. Two studies were not able to replicate this finding [ 84 , 86 ] ( Table 1 ).…”
Section: Studies In Humansmentioning
confidence: 99%
“…These nucleic acids are often contained within exosomes released into the bloodstream from blood cells, the brain, and the spine [48]. Advances in sequencing technology have allowed higher level molecular profiling of blood, CSF, and more recently urine and saliva, to investigate nucleic acids within epilepsy outside of the exosome [49][50][51]. While evidence on the utility of circulating nucleic acids in epilepsy is underdeveloped in comparison to other diseases, we review the current landscape below.…”
Section: Nucleic Acids (Cfdna and Mirna And Trnas)mentioning
confidence: 99%